Forensic approach to predict film thickness of reacted and activated rubber (RARX) modified asphalt mixtures. (14th September 2020) - Nanjegowda, Vinay Hosahally; Silva, Francisco; Sousa, Jorge B.; Way, George B.; Biligiri, Krishna Prapoorna
Abstract : The major objective of this study was to arrive at an optimum threshold asphalt binder film thickness, T f ∗ and develop T f ∗ predictive equation that includes materials and mixture properties, which could be used in all future forensic assessment of asphalt mixtures. Also, 18 field asphalt mixtures constructed as test sections were investigated for their field performance and correlated with T f ∗ . Furthermore, the performance criteria set by Arizona department of transportation (ADOT) in the USA to assess the field mixtures were related to T f ∗ established in this study. An optimum T f ∗ of 12 µ was selected as the threshold magnitude for asphalt mixtures that incorporates activated crumb rubber modified products, termed RARX. It was found that with increase in the overall cumulative surface area ( SA ) of the mix matrix, the required binder content also increased, in turn decreasing T f ∗ . T f ∗ predictive equation encompassing materials properties and associated volumetrics was established as a best-fit nonlinear regression model that had excellent statistical measures: R 2 = 99.8%; Se /Sy = 0.0447. It is noteworthy that the predictive model was established using the robust concept that introduced utilisation of SA of the whole mixture matrix, including, those that of SA of aggregate fractions not estimated by current models. Based on the methodical approach followed in this study to calculate T f ∗, it is recommended that more amount of RARX be tried in other mixtures to enhance pavement performance. The current study involved only 18 field asphalt mixtures, amongst which six were without RARX. So, it is suggested that additional field sections be placed and monitored for their performance keeping in mind the volumetrics and specifically, T f ∗, which can potentially be a quality control parametric assessor for field performance forensic evaluation, and that which becomes an integral characteristic in perpetual pavement design philosophy.